Managing IT in construction/managing construction for tomorrow proceedings of the 26th International Conference on IT in Construction & 1st International Conference on Managing Construction for Tomorrow, Istanbul Technical University, Istanbul, Turkey, 1-3 October 2009 /: proceedings of the 26th International Conference on IT in Construction & 1st International Conference on Managing Construction for Tomorrow, Istanbul Technical University, Istanbul, Turkey, 1-3 October 2009. (©2010) - Unknown
No abstract available